2014
DOI: 10.2134/agronj2012.0326
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yield Response to the Solar Corridor in Upstate Missouri

Abstract: The solar corridor uses ultra wide‐row (152‐cm) corn (Zea mays L.) and reduced seeding rates to maximize photosynthesis of lower leaves and maintain or increase yield potential of the crop. But in common practice, seeding rates for corn have increased and row spacing decreased for early canopy development to maximize light interception, reduce weed interference, reduce herbicide applications and costs, and maintain conservation compliance. However, wide rows help manage disease in some instances. Relay‐intercr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Twin rows were 19 cm apart, similar in previous studies (Nelson and Smoot, 2009) but were on 152‐cm centers to provide the corridors (see Fig. 1 in Nelson, 2014). Details on tillage, planting, and harvesting procedures and fertilizer and herbicide applications are provided in Nelson (2014).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Twin rows were 19 cm apart, similar in previous studies (Nelson and Smoot, 2009) but were on 152‐cm centers to provide the corridors (see Fig. 1 in Nelson, 2014). Details on tillage, planting, and harvesting procedures and fertilizer and herbicide applications are provided in Nelson (2014).…”
Section: Methodsmentioning
confidence: 98%
“…A field trial evaluating response of corn hybrids to the SCCS was established in 2011 near Novelty, MO, in Knox County (40°01′ N, 92°11′ W) (Nelson, 2014) and repeated in 2013 near Columbia, MO, in Boone County (38°54′ N, 92°12′ W). The trials were established on a Putnam silt loam (fine, smectitic, mesic, Vertic Albaqualfs) in Knox County and Mexico silt loam (fine, smectitic, mesic, Aeric Vertic Epiaqualfs).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited field trials have shown the potential for increased maize yields of specific hybrids, however, more studies must be conducted to overcome some of the challenges of the solar corridor for it to be a fully successful sustainable crop production system [4,15]. Early work with the SCPS demonstrated that specific maize hybrids could be selected for high yield performance [2,4], however, seed sources of these classical hybrids are limited or have disappeared as alternative germplasm has been developed for current industrial maize production.…”
Section: Opinionmentioning
confidence: 99%